Evaluation of Canada’s biomass policy in comparison to its Nordic counterparts - Sembrano, Gabriel (My University, 2023)
The transition towards renewable energy sources is considered one of the main mitigation measures combating the effects of climate change. The use of renewable energy, particularly those derived from forest biomass, is gaining traction in Canada and the international scene. Nordic countries are seen as leaders in this field and has therefore developed policy programs supporting the use of forest-based biomass energy. This review focuses on four factors influencing the policy development process: (1) Forest governance, (2) Land ownership, (3) Stance on natural gas, and (4) the jurisdiction’s policies supporting the use of forest-based energy. The result of this review shows that policy schemes must be coherent at all levels of the government. In addition, all major industries strongly support policy programs, particularly those incentivizing the transition towards renewable alternatives. Lastly, quantifiable goals must be developed to provide a measure on the effectiveness of such schemes.
Keywords: Biomass; Incentive; Jurisdiction; Policy; Renewable energy